The Use of Cohesive Devices and Generic Structure in Students’ Recount Texts of UIN Alauddin Makassar (The Journal of Educational Development, 2021)
Cohesive devices have a significant role to play in producing text writing. Because cohesive devices do not just show one unity in a text but also express the sustainability of a sentence that is between one sentence and a sentence that other and even between one paragraph with another paragraph in the text. The generic structure function is making the sentences in a text neater and more structured. This research aimed to evaluate the use of cohesive devices and generic structure in students’ recount text at the English Department of UIN Alauddin Makassar. This study adopted the theory of Hasan & Halliday (1976). The result shows that the most contribution of cohesive devices in students’ recount texts is provided by conjunction especially the use of causal conjunction. Then, it followed by the use of reference, substitution, and ellipsis. It indicated that most of the students used the conjunctions in their recount texts to realize the relationship of how the subsequent sentence or clause should be linked to the following sentence. Then, based on the evaluation of the use of generic structures in students’ recount texts, it is can be concluded that all of the thirty recount texts of UINAM fifth-semester used the orientation, events, and re-orientation in their recount texts. Further, both cohesive devices and generic structures are related to each other to create a good text. The use of cohesive devices and generic structures in students’ recount texts affects the quality of texts that are produced by the students. It means that the use of cohesive devices and generic structures is very important in developing a good text.